Effect of nitrogen and mineral composition of the high-concentrated wort made from starch-containing raw materials on the cultivation of yeast - Shiyan, Peter; Mudrak, Tatiana; Kyrylenko, Roman; Kovalchuk, Svetlana (Eastern-European Journal of Enterprise Technologies, 2017)
We theoretically substantiated and experimentally confirmed the feasibility of enriching highly-concentrated wort made from starch-containing raw materials with nitrogen and mineral nutrition for yeast cells. The influence of nitrogen nutrition, as amine and ammoniac nitrogen, as well as mineral nutrition as nanoparticles and ions of metals was investigated. It was established experimentally that in the course of cultivating the yeast on wort with a concentration of 20, 28 % DS, a necessary precondition is the adjustment of nitrogen nutrition through additional introduction of glycine to serve as amine nitrogen, the concentration of 0.7 g/dm3 of wort, and ammoniac nitrogen (to serve as carbamide) in the amount of 800 g/m3, which would make it possible to increase the concentration of yeast cells to 280−430 mln/cm3 in the process of culturing the yeast depending on the concentration of wort and the type of nitrogen nutrition, respectively. Based on results of the present research on the influence of mineral nutrition in the nano- and ionic form on the yeast-generation process, it was determined that the largest positive effect on the synthesis of yeast cells was exerted by Zn and Mg and the mixtures of these metals, both in nano- and in ionic form, whose concentration was 1.2 mg/cm3 and 50 g/m3, respectively; in this case, the number of yeast cells ranged from 360 to 480 mln/cm3 depending on the concentration of wort and the type of mineral nutrition. We have proven the feasibility of cyclic use of mineral nutrition, both in ionic and in nano forms, when cultivating yeast, in order to obtain cells with high physiological-biochemical activity. The use of mineral and nitrogen nutrition allowed us not only to obtain a high concentration of yeast cells, but also reduce the duration of yeast-generation to 15–20 hours and ensure their high regenerative and physiological activity during fermentation of wort with high concentrations of dry substances